Exactly the same but completely different: A thematic analysis of Clinical Psychologists' conceptions of Autism across genders. (June 2019) - Muggleton, Joshua T.B.; MacMahon, Ken; Johnston, Katrina
Highlights: Clinicians think the definition of autism is gender neutral. Girls and boys are thought to be equally affected by autism. Girls with autism have a different presentation. Autism is about social communication and interaction, although RRBIs are important. Culture effects observers interpretations of behavior. Abstract: Background: Existing diagnostic criteria for autism do not indicate gender differences in the expression of core domains of the condition. Yet, an increasing body of research suggests that pronounced gender differences do exist. It may be that current diagnostic criteria do not capture individuals with a gender-specific presentation of autism. Method: Fourteen Clinical Psychologists who routinely conduct autism assessments were interviewed about their conceptions of autism in children, and any gender differences therein. Thematic analysis was used, with thematic networks developed from data. Results: Autism itself was conceptualised by clinicians as gender-neutral, with social communication and interaction at its core. Girls and boys were thought equally affected by autism, but girls were viewed as likely to be more socially aware and socially motivated, better at emotional recognition, and more internalising in their stress coping response, altering their presentation. Further, culture affects how a person with autism acts, and observers' interpretations of these behaviours. Conclusions: While existing diagnostic criteria provide appropriate coverage for the core features of autism, they may not capture everything about autism. Participants felt that restricted and repetitive behaviours and interests were less central to the concept of autism than social communication difficulties. Gender differences were identified in areas closely related to, but distinct from the diagnostic criteria. Consideration of these gender-specific presentations during assessment may aid diagnosticians. Participants' themes provide an experienced-based narrative for understanding the interaction between autism and gender.